Network analytics for drug repurposing in COVID-19. Issue 1 (7th December 2021) - Siminea, Nicoleta; Popescu, Victor; Sanchez Martin, Jose Angel; Florea, Daniela; Gavril, Georgiana; Gheorghe, Ana-Maria; Iţcuş, Corina; Kanhaiya, Krishna; Pacioglu, Octavian; Popa, Laura lona; Trandafir, Romica; Tusa, Maria Iris; et al.
Abstract: To better understand the potential of drug repurposing in COVID-19, we analyzed control strategies over essential host factors for SARS-CoV-2 infection. We constructed comprehensive directed protein–protein interaction (PPI) networks integrating the top-ranked host factors, the drug target proteins and directed PPI data. We analyzed the networks to identify drug targets and combinations thereof that offer efficient control over the host factors. We validated our findings against clinical studies data and bioinformatics studies. Our method offers a new insight into the molecular details of the disease and into potentially new therapy targets for it. Our approach for drug repurposing is significant beyond COVID-19 and may be applied also to other diseases.